DAMPAK AKSESI ICCPR TERHADAP PENCEGAHAN PRAKTIK PEMBUNUHAN DI LUAR HUKUM DALAM PERSPEKTIF INDONESIA - Ashri, Munif (Faculty of Law, Parahyangan Catholic University, 2025)
Indonesia has made notable progress in institutionalizing human rights norms through the ratification and accession of various international treaties. Despite these advancements, violations of the right to life, particularly in the form of extrajudicial killings, continue to occur. This study investigates the extent to which Indonesia’s accession to the International Covenant on Civil and Political Rights (ICCPR) has influenced the protection of individuals from such violations. Employing a socio-legal approach, the research assesses institutional reforms following the ICCPR accession and analyzes specific cases, including the 2020 extrajudicial killings of Pastor Yeremia Zanambani and members of the Islamic Defenders Front (FPI). Findings reveal that, although legislative and policy reforms have been introduced to strengthen the right to life, their implementation remains inadequate. The persistence of extrajudicial killings is primarily attributed to the incomplete Security Sector Reform (RSK) process and the deeply rooted culture of impunity, which often results in lenient sentences or acquittals for alleged perpetrators. This study emphasizes the urgent need to advance the RSK agenda and address impunity through concerted efforts by key institutions, including the judiciary.